ANALISIS PENGELOLAAN ARSIP DINAMIS INAKTIF DI PUSAT ARSIP UNIVERSITAS NEGERI SURABAYA UNTUK MEWUJUDKAN GOOD GOVERNANCE - AYU WIDYANINGTYAS, GITHA (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2016)
ABSTRACT Organizations cannot be separated from administrative activities in which there are series of office work to carry out vision and mission as well as in decision-making. Basis for a decision to a leader can come from archives. Archive as a central memory and supervisor activities organization does need to get a good handling in order to archive physical awake and contents, if necessary; the archive can be quickly and accurately rediscovered for help in completing task. Because of archive is a valuable asset to organization. This study aims to determine the management of the archive includes the step of receiving, storing, maintenance, depreciation and culling on the inactive dinamic archive in central of archive State University of Surabaya to realize good governance. This type of research is descriptive qualitative. The subject in this research were archivists and archive management staff who directly doing archive management in central of archive Universitas Negeri Surabaya with total five people. The techniques of data collection that used are interview, observation and documentation. The technique of data analysis that used are consist of data reduction, data presentation and conclusion. While the validity of the data using a triangulation technique source. The results showed that the reception archive tasteless. The results showed that acceptance comes from the archive of finance, personnel and equipment of Administration Bureau of the Public Administration and Finance Universitas Negeri Surabaya. Archive storage system using alphabetical, chronological subject and the principle of centralization. Maintenance records using vacuum cleaner, broom, and feather duster because plan expenditure budget is still the one with of Administration Bureau of the Public Administration and Finance Universitas Negeri Surabaya. Depreciation is based on the Archive Retention Schedule. Demolition of the archive is using the method of paper shredder, burning and sold to company. Efforts Archives realize good governance provided through service excellence for the borrower archives, archives remain in good physical and information contained therein to assist management in making policy whose output can be felt by the public. The central of archive can work well if it has organization structure. In this case, it has authorities to make a work program and policy to manage the archive especially inactive dynamic archive to realize good governance. Keywords: Archive Management, Good Governance